(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the context of digital transformation and increasing competition, certified project management professionals (PMPs) play a key role in service companies. Their expertise in the application of PMP standards allows them to effectively plan and control projects aimed at optimizing business processes. This leads to increased productivity, improved service quality, and sustainable development. The article examines approaches, methodologies, and practical examples of the application of PMP standards in service organizations, and analyzes their impact on productivity, service quality, and sustainable development.